Pengaruh Budaya Organisasi, Kompetensi Dan Kepemimpinan Terhadap Kinerja Karyawan Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan Wilayah Sumbagsel (MOTIVASI, 2022)
This study aims to determine the influence of organizational culture competence and leadership on the performance of employees of the Social Security Administering Agency (BPJS) Manpower in the South Sumatra Region. The research method used in this study is causal research (verificative), which is a study that examines the relationship (influence) between one variable and another. The population in this study were employees of BPJS Employment from South Sumatra as. The type of data used in this study is primary data, namely data obtained directly from the results of questionnaires given to respondents. The coming test was carried out using the validity and reliability test methods. The results of the study indicate that there is an influence of Organizational Culture Competence and Leadership Style on the Performance of Employees of the Social Security Administering Body (BPJS) for the Sumbagsel Region.